The external evaluation of educational achievements in higher education: results and indicators in 2014. (Journal of Educational Sciences, 2016)
This article presents the results of an external evaluation of educational achievements in 2012-2014. According to the results of a comparative analysis of EVEA in the context of higher education institutions, 6 areas of specialties and disciplines. According to the results of EVEA 2013 and 2014 the cluster analysis on the traditional system of evaluation in the context of the status of universities (national, state, and private joint-stock) are conducted. By the end of 2014 EVEA in a diagram shows the comparative data of test results full-time students and part-time offices. In terms of the status of universities conducted a cluster analysis in the disciplines of the specialty «Jurisprudence». Outcome indicators are presented in the form of EVEA and traditional credit evaluation system (2013-2014 y.). In «Social sciences, economics and business», the comparative analysis, data for the 2013-2014. one of the state universities, one private university, as well as indicators of the republic. The data on the number of students who passed EVEA as «excellent», «good», «satisfactory» and «unsatisfactory». The article can be seen annual dynamics of EVEA. The website of the National Testing Centre www.testcenter.kz
Keywords: monitoring of education; external evaluation of educational achievements; cluster analysis